Compulsory social service matching market for physicians in Colombia (2015)
In Colombia, physicians must work during a year to fulfill a compulsory social service known as año rural. This service constitutes an entry-level labor market which can be modeled as a many-to-one matching market. To match physicians with hospitals, a centralized and equiprobable random drawing is employed in the market. This random mechanism is evaluated here by using axioms of ex-post stability, ex-post efficiency and strategy-proofness. It is underlined in this paper that agents in the market have identified these axioms as a matter of interest. A formal proof shows that the random mechanism violates these axioms.